2013
DOI: 10.1007/s13730-013-0084-z
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine dynamics in a 14-year-old girl with tubulointerstitial nephritis and uveitis syndrome

Abstract: Tubulointerstitial nephritis and uveitis (TINU) syndrome, which was first described in 1975, has been reported in more than 130 patients, mostly in adolescent or young women. Although data concerning the etiologic background of this inflammatory disease are limited, several humoral factors, including cytokines, have been reported in association with the disease. Here, we report a case of TINU in a 14-year-old girl, whose renal and ophthalmological improvement was associated with the decrease of serum levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The same group showed that urinary TNF-α was also higher in a large series of ATIN cases compared to other causes of inflammatory kidney disease, and that urinary TNF-α correlated well with the number of TNF-α-positive cells in the renal biopsy [ 24 ]. Aoyagi et al reported the value of serum TNF-α levels in the follow-up of a case of TINU, which dramatically decreased during the first week after treatment initiation [ 25 ]. Moledina et al found higher urinary IL-9 along with higher TNF-α levels in patients with ATIN.…”
Section: Serum and Urine Cytokines And Chemokinesmentioning
confidence: 99%
“…The same group showed that urinary TNF-α was also higher in a large series of ATIN cases compared to other causes of inflammatory kidney disease, and that urinary TNF-α correlated well with the number of TNF-α-positive cells in the renal biopsy [ 24 ]. Aoyagi et al reported the value of serum TNF-α levels in the follow-up of a case of TINU, which dramatically decreased during the first week after treatment initiation [ 25 ]. Moledina et al found higher urinary IL-9 along with higher TNF-α levels in patients with ATIN.…”
Section: Serum and Urine Cytokines And Chemokinesmentioning
confidence: 99%